PERKEMBANGAN CABANG OLAHRAGA SURFING SEBAGAI SALAH SATU SPORT TOURISM DI KAWASAN PANTAI SENGGIGI KABUPATEN LOMBOK BARAT - Ahmad Jaelani; Elya Wibawa Syarifoeddin; Fitri Anggraeni (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2024)
This study analyzed the development of surfing as a sport tourism attraction in the Senggigi Beach area, West Lombok Regency. The study used a descriptive quantitative design with questionnaire-based data collection. Respondents consisted of 40 stakeholders, including local surfing athletes, surfing organization administrators, MSME actors, outdoor-equipment rental providers, and villa owners around Senggigi Beach. Data were analyzed descriptively using percentages. The findings show that accessibility to the location (80%) and the presence of local MSMEs (70%) were the strongest supporting factors for surfing-based sport tourism development. Meanwhile, tourism infrastructure management (60%) and the availability of surfing training (55%) were rated as moderate, whereas cooperation with government stakeholders (45%) emerged as the weakest aspect. These results indicate that Senggigi has promising potential to strengthen surfing as a sport tourism product, but better governance, supporting facilities, and coordinated stakeholder collaboration are still needed to support sustainable destination development.